Simulation and optimization of novel configurations of triple absorption heat transformers integrated to a water desalination system - Khamooshi, Mehrdad; Parham, Kiyan; Egelioglu, Fuat; Yari, Mortaza; Salati, Hana (Elsevier Science Bv, 2014)
A thermodynamic analysis of six different configurations of triple absorption heat transformer systems (TAHTs) utilizing H2O/LiBr as the working pair which is integrated into water desalination systems is conducted in this study. The energy source of the desalination system is provided by the high temperature heat of the absorbers of TAHTs by utilizing the waste heat from a textile factory. A computer program is developed in the EES (Engineering Equation Solver) to study the performance of the system such as; COP, ECOP, distilled water, and absorber utilized heat, and also to optimize them in six different configurations. It is shown that modified configurations of TAHTs can increase the COP and fresh water productivity rather than that of conventional systems. The results indicated that the optimized amount of distilled water produced by the last configuration which is 0.1307 kg/s can supply 1131 residential units. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Triple absorption heat transformer; LiBr/H2O; Desalination; Configuration; Economizer effectiveness